Zadania Państwowej Straży Pożarnej wobec zagrożenia terroryzmem w Polsce - Kopa, Dariusz; Imielski, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article examines the tasks of the State Fire Service in the face of terrorist threats in Poland. The State Fire Service is an important component of the national security system. As a well-trained and well-equipped country-wide agency with a well-developed organisational structure on the three administrative levels — subregional, regional and national — it can carry out tasks in an emergency, all-day, all-year-round mode within the territory of Poland, tasks relating to broadly defi ned rescue operations, including recognition of threats and rescue operations necessitated by acts of terrorism, despite the fact that in this case it is only an auxiliary service helping the agencies designated by law to combat such threats. The need for rescue services, security services and investigation services to collaborate in the case of a terrorist threat or suspicion of a terrorist threat has greatly expanded the operational possibilities of the State Fire Service, especially with regard to specialist rescue operations.
Keywords: Pańswtowa Straż Pożarna; terroryzm; bezpieczeństwo narodowe; zagrożenie bezpieczeństwa